Differential uptake and oxidative stress response in zebrafish fed a single dose of the principal copper and zinc enriched sub-cellular fractions of Gammarus pulex - Khan, Farhan R.; Bury, Nicolas R.; Hogstrand, Christer (Aquatic toxicology, 2010)
The sub-cellular compartmentalisation of trace metals and its effect on trophic transfer and toxicity in the aquatic food chain has been a subject of growing interest. In the present study, the crustacean Gammarus pulex was exposed to either 11 μg Cu l −1, added solely as the enriched stable isotope 65Cu, or 660 μg Zn l −1, radiolabeled with 2MBq 65Zn, for 16 days. Post-exposure the heat stable cytosol containing metallothionein-like proteins (MTLP) and a combined granular and exoskeletal (MRG + exo) fractions were isolated by differential centrifugation, incorporated into gelatin and fed to zebrafish as a single meal. Assimilation efficiency (AE) and intestinal lipid peroxidation, as malondialdehyde (MDA) were measured. There was a significant difference ( p < 0.05) between the retention of the MTLP-Zn (39.0 ± 6.4%) and MRG + exo-Zn (17.2 ± 3.7%) and of this zinc retained by the zebrafish a significantly greater proportion of the MTLP-Zn feed had been transported away from the site of uptake. For 65Cu, although the results pointed towards greater bioavailability of the MTLP fraction compared to MRG + exo during the slow elimination phase (24–72 h) these results were not significant ( p = 0.155). Neither zinc feed provoked a lipid peroxidation response in the intestinal tissue of zebrafish compared to control fish (gelatin fed), but both 65Cu labeled feeds did. The greater effect was exerted by the MRG + exo (2.96 ± 0.29 nmol MDA mg protein −1) feed which three-fold greater than control ( p < 0.01) and almost twice the MDA concentration of the MTLP feed (1.76 ± 0.21 nmol MDA mg protein −1, p < 0.05). The oxidative stress response produced by Zn and Cu is in keeping with their respective redox potentials; Zn being oxidatively inert and Cu being redox active. These results are similar, in terms of bioavailability and stress response of each feed, to those in our previous study in which 109Cd labeled G. pulex fractions were fed to zebrafish. Thus it appears that when a metal (Cu or Cd) has the potential to cause cytotoxicity via lipid peroxidation, a feed consisting of a largely unavailable fraction (MRG + exo) causes a greater intestinal stress response than the more bioavailable (MTLP) feed.